How South Korean women leaders respond to their token status: assimilation and resistance. Issue 4 (8th August 2021) - Cho, Yonjoo; Kim, Sehoon; You, Jieun; Han, Heeyoung; Kim, Minjung; Yoon, Sokyum
ABSTRACT: As there are only a few women leaders in almost all sectors in South Korea, they face difficulties in taking leadership roles in the workplace where traditional cultural values and male-dominated organizational culture coexist. The purpose of this study was to examine how three concepts of tokenism theory (visibility, contrast, and assimilation) applied to a Korean context and how token women leaders responded to the challenges they face in the workplace. Using a secondary analysis of qualitative data aimed at addressing new research questions, we reanalysed data from 107 women leaders' interviews collected from previous research and identified five themes: culture, visibility, contrast, assimilation, and resistance. By revealing a dynamic interplay of factors influencing women leaders' experiences through the lens of tokenism theory, we found that women leaders assimilated to meet the dominant male group's expectations but a few managed to resist in their own way to bring change in organizations. This study is uniquely Korean because women leaders' resistance to their token status has never been captured in research on tokenism in western contexts.